Implementasi Hubungan Ilmu, Budaya, dan Ekonomi pada Lembaga Pendidikan Islam Indonesia - Ahmad Bilal Almagribi; Muslimah Muslimah (Universitas Negeri Medan, 2021)
ABSTRACTThis research is intended to find the relationship between science, culture, and economics as well as their implementation in Islamic education institutions (IEI). The method used is descriptive qualitative with literature review. The results showed that the relationship between science, culture and economy based on Koentjaraningrat’s cultural elements theory is general and specific, the elements of the knowledge system are the same as science and the livelihood system is the same as the economy. The seven elements of culture have been implemented in the IEI: (1) The language elements used are Indonesian, regional languages, Arabic, English, and other foreign languages. (2) The elements of the knowledge system in the IEI are leaning towards traditionalist or modernist currents. (3) The social organization elements in the IEI can be under the government or foundations with each institution having a member level. (4) Elements of technology owned by IEI consist of laboratories of various types and facilities of different quality at each location. (5) The element of livelihood at IEI is in the form of compulsory contributions, donations, baitul mals, cooperatives, or rental of business stalls. (6) The religious element in each IEI is of course based on Islamic teachings by providing opportunities for non-Muslims to study at several Islamic universities. (7) Art elements implemented by the IEI include calligraphy, tambourine, reading the Qur'an, speech, and nasheed.KEYWORDSScience, Culture, Economy, Implementation, Islamic Education Institution.